Flexural Strength Study of Laboratory-Produced Freshwater and Saline Ice and Beaufort Sea Ice with Granular Layer, 2023-2024 ... - Murdza, Andrii; Schulson, Erland; Edington, David (NSF Arctic Data Center, 2024)
A granular layer can form on top of sea ice due to processes like snowfall, wind-blown snow accumulation, or freeze-thaw cycles, which create a distinct, less consolidated ice layer that affects the overall mechanical properties of the ice. Understanding the mechanical properties of ice with a thin granular layer is essential for predicting and mitigating the impacts of climate change on polar environments, global sea levels, and the safety of human activities in these regions. A series of flexural experiments were performed on columnar-grained ice of three kinds atop which a layer of freshwater granular ice had been bonded: first-year sea ice harvested from the winter cover on the Beaufort Sea, saline ice produced in the laboratory, and freshwater ice also produced in the laboratory. These new experiments have revealed that a thin layer of granular ice bonded to salty and to salt-free columnar-grained ice increases flexural strength when the material is rapidly bent to the point of brittle fracture. When ...